2018
DOI: 10.1063/1.5054870
|View full text |Cite
|
Sign up to set email alerts
|

Rewetting and boiling in jet impingement on high temperature steel surface

Abstract: Interface topologies and boiling phenomena are observed within the water jet impingement zone during quenching of a high temperature (300 °C–900 °C) steel plate by direct optical observations. Stable film boiling may occur, but surface asperities may easily penetrate the vapor film and interact with the flowing liquid. By cooling down more rapidly than the remaining solid surface, such asperities act as a kind of micro-fin. Rather surprisingly, non-coalescing bubbles on top of the thin vapor film have been obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 41 publications
3
41
1
3
Order By: Relevance
“…The observations reported in the above are typical for sandblasted surfaces with initial plate temperature in the range 300-650 • C. The complete recording of rewetting on a sandblasted surface and a detailed video of the flashing pattern are available on the online version of this paper as movie 1. Figure 4 corresponds to a series of snapshots taken from the high-speed recordings during the quenching process of a smooth plate at 650 • C. As reported before by Leocadio, van der Geld & Passos (2018), an initial film boiling period is observed (figure 4a). The film boiling regime is characterized by the presence of small moving white spots, which do not condense or coalesce.…”
Section: Sandblasted Surfacesupporting
confidence: 64%
“…The observations reported in the above are typical for sandblasted surfaces with initial plate temperature in the range 300-650 • C. The complete recording of rewetting on a sandblasted surface and a detailed video of the flashing pattern are available on the online version of this paper as movie 1. Figure 4 corresponds to a series of snapshots taken from the high-speed recordings during the quenching process of a smooth plate at 650 • C. As reported before by Leocadio, van der Geld & Passos (2018), an initial film boiling period is observed (figure 4a). The film boiling regime is characterized by the presence of small moving white spots, which do not condense or coalesce.…”
Section: Sandblasted Surfacesupporting
confidence: 64%
“…The water jet system has been upgraded to allow for installation of both a circular jet nozzle of 9 mm diameter and a planar slit jet nozzle of 2x50 mm. As reported elsewhere [1], [7], a borescope and high speed camera arrangement enables the direct observation of the boiling activity in the jet stagnation zone. Additionally, a side view high speed camera is installed to record the jet and flow development on the complete test plate.…”
Section: Methodsmentioning
confidence: 90%
“…For this reason, quenching by water jet impingement has been widely studied in literature. However, most of the experimental studies reported in literature have focused on static surfaces [1]- [3] or surfaces moving at maximum speeds of 1.5 m/s [4]- [6], much lower than the real ROT conditions. In order to obtain heat transfer predictions that are applicable and representative of the ROT process, the effect of high surface speeds on the thermal boundary layer must be considered and studied experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…), [4,5] plate parameters (roughness, initial cooling temperature, etc. ), [6,7] and parameters (shape, number, etc.) [8,9] of the thin plates used.…”
Section: Introductionmentioning
confidence: 99%